Nanosense: Nonsurgical treatment of superficial cancer by (PLAN) - Arkady Valentinovych Khromov; Maysaa Banay Zubairi; Hasan Mohammad Hasan Alhejoj; Zinah Azzam Abdulwahhab Alshareeda; Omar Saleh Abdulkader (Pensoft Publishers, 2024)
Under current development is Nanosense, a medication designed for the nonsurgical treatment of superficial cancer via pulsed laser ablation of nanoparticles (PLAN). Nanosens is a stable dispersion of phthalocyanine zinc nanoparticles in a physiological solution. The technology for obtaining stable dispersions of zinc phthalocyanine ensures a shelf life of over two years. This article presents preliminary data from preclinical studies of the Nanosens formulation. Results were obtained on the effectiveness, pharmacokinetics, and biodistribution of the Nanosens drug in mice, as well as toxicity and allergy studies. When tested at therapeutic doses (1 TD = 7 mg/kg) ranging from 1 to 10 TD for acute toxicity and from 1 to 30 TD for chronic toxicity, no signs of intoxication leading to death were observed in animals. However, at the maximum dose, individual organs and tissues exhibited a blue coloration.